2004
DOI: 10.1207/s15327078in0503_1
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory Redundancy Enhances Memory in Bobwhite Quail Embryos

Abstract: Information presented concurrently and redundantly to 2 or more senses (intersensory redundancy) has been shown to recruit attention and promote perceptual learning of amodal stimulus properties in animal embryos and human infants. This study examined whether the facilitative effect of intersensory redundancy also extends to the domain of memory. We assessed bobwhite quail chicks' ability to remember and prefer an individual maternal call presented either unimodally or redundantly and synchronously with patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…For example, the greater amount of information provided through multisensory stimulation could increase infants' general arousal and provide them with more information through which to compare numerical values. To discount this hypothesis, prior studies asking whether intersensory redundancy enhances cognitive, perceptual, and even social development have run control conditions in which asynchronous or non-redundant multisensory information is presented to the infant (i.e., Bahrick and Lickliter, 2000;Flom and Bahrick, 2007;Lickliter et al, 2002Lickliter et al, , 2004. In all such situations, infants fail to discriminate the property being tested unless it is synchronously and redundantly specified across multiple modalities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the greater amount of information provided through multisensory stimulation could increase infants' general arousal and provide them with more information through which to compare numerical values. To discount this hypothesis, prior studies asking whether intersensory redundancy enhances cognitive, perceptual, and even social development have run control conditions in which asynchronous or non-redundant multisensory information is presented to the infant (i.e., Bahrick and Lickliter, 2000;Flom and Bahrick, 2007;Lickliter et al, 2002Lickliter et al, , 2004. In all such situations, infants fail to discriminate the property being tested unless it is synchronously and redundantly specified across multiple modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Quail embryos are able to learn a maternal call significantly faster when the rate, rhythm, and duration of the call is synchronized with a light, thus providing intersensory redundancy, than when the call is presented alone (Lickliter, Bahrick, & Honeycutt, 2002). Further, Lickliter, Bahrick, and Honeycutt (2004) found that chicks receiving redundant bimodal stimulation of the temporal features of the maternal call prenatally remembered the call four times longer into postnatal development than chicks receiving prenatal unimodal exposure.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Both animal and human infants are particularly adept at attending to amodal information early in development, since amodal information, such as intensity, tempo, and frequency, is present across sense modalities and can therefore be perceived concurrently. The synchronous pairing of two (or more) sense modalities recruits selective attention, thereby improving subsequent learning and memory (Bahrick & Lickliter, 2000;Lickliter, Bahrick, & Honeycutt, 2004).…”
Section: Enrichment Perceptual Narrowing and Response To Noveltymentioning
confidence: 99%
“…This experiment manipulated prenatal auditory stimulation in bobwhite quail embryos from the onset of auditory function to assess whether it is possible to keep the perceptual narrowing window open and effectively interfere with the emergence of a species typical auditory preference postnatally. Classic and contemporary work with precocial birds has demonstrated a robust effect of unimodal auditory and bimodal auditory/visual or auditory/vestibular stimulation on facilitating learning and memory for a species typical maternal call (Lickliter, Bahrick, & Honeycutt, 2004;Lickliter & Hellwell, 1992;Honeycutt & Lickliter, 2001;Vaillant, Bahrick, & Lickliter, 2009). However, these methods have yet to be applied to perceptual narrowing.…”
Section: Unimodal Perceptual Narrowing (Preventing Narrowing Through mentioning
confidence: 99%